Correlation between Soil Carbon Potential and Soil Quality Index in Various Types of Dry Land Use in Aceh Besar District - Umar H A; Endiyani Endiyani; Sri Agustina; Irhami Irhami; Yusran Akbar (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2023)
Soil quality is a useful concept when assessing the sustainability of an agricultural business and demonstrating the ability of soil to maintain plant and animal productivity, improve water and air quality, and protect human health. SQI is a soil variable with the following characteristics: 1) well correlated with ecosystem processes; 2) integration of physical, chemical, and biological soil properties; 3) good sensitivity to human-induced soil changes; 4) simple measurement and interpretation; and 5) Reproducibility Soil quality index (SQI) is a diagnostic procedure to evaluate soil function and overall health. This research was carried out on a unit of land in a dry area in Aceh Besar District with a study area of 239,439.63 ha. Analysis of biomass samples and soil samples was carried out at the Laboratory of Soil and Plant Sciences and Soil Physics Laboratory, Faculty of Agriculture, University of Syiah Kuala. The tools used in this study include a set of computers with the Microsoft Windows 10 operating system that are equipped with several software for analysis, writing instruments, and other supporting tools. The main materials used in this study were soil samples, tree diameter measurement data, and land use maps, including geology, climate, slope class, soil, and topography. The results of the correlation analysis test showed a value of 0.6358. This shows that the relationship between soil C potential and soil quality index is a strong correlation. The distribution of carbon in the soil also has a close relationship with the soil quality index and is an effort to maintain carbon stocks in the soil. C - organic content is a very important parameter in compiling soil quality index criteria. Soil quality can be affected by many factors, such as parent material, environmental factors, land use type, and human activities. The percentage of soil organic C is an indicator of the percentage of soil organic matter (BOT), and BOT is able to improve soil structure and aggregates. Soil organic carbon (SOC) concentration is closely related to soil quality and vegetation productivity. This relationship occurs because of the many contributions of soil carbon to soil properties such as the improvement of soil structure and water retention, provision of cation exchange capacity, and supply of plant nutrients through mineralization. This effect is especially important in small-scale tropical farming systems where the use of external inputs is often limited, and SOC concentrations have been positively correlated with yield levels for a variety of tropical soils.